2019
DOI: 10.1293/tox.2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Location and dynamic changes of inflammation, fibrosis, and expression levels of related genes in SiO<sub>2</sub>-induced pulmonary fibrosis in rats <i>in vivo</i>

Abstract: Silicosis is a serious occupational disease characterized by pulmonary fibrosis, and its mechanism and progression have not been fully elucidated yet. In this study, silicosis models of rat were established by a one-time dusting method, and the rats were sacrificed after 30, 60, and 120 days (herein referred to as the 30, 60, and 120 days groups, respectively). The rats without dust exposure were used as the control. The lungs were removed to observe pathological changes using hematoxylin and eosin and Masson’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…This finding is consistent with the previous investigation on A549 cells, 56 yet with a much lower exposure dose in our case, potentially accounting for the loss of epithelial integrity shown in in vivo works. 54,55 Taken together, these data indicate that the organoid-based culture can be successfully applied to test the toxicity of nanoparticles, such as nano-SiO 2 , and presumably, the toxicity of chemicals.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…This finding is consistent with the previous investigation on A549 cells, 56 yet with a much lower exposure dose in our case, potentially accounting for the loss of epithelial integrity shown in in vivo works. 54,55 Taken together, these data indicate that the organoid-based culture can be successfully applied to test the toxicity of nanoparticles, such as nano-SiO 2 , and presumably, the toxicity of chemicals.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Mechanical grinding that breaks quartz crystal for production may lead to the formation of crystal surface defects and high exposure of heterogeneous silanol groups, thus significantly increasing its biological activity (Turci et al, 2016). The diameter of SiO 2 that induces silicosis usually is less than 5 µm (Xu et al, 2019; Zhang et al, 2019a). Previous studies have shown that smaller size implies greater toxicity (Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Its pathological features include early infiltration of inflammatory cells, persistent pulmonary inflammation, excessive deposition of extracellular matrix (ECM), interstitial fibrosis, and formation of silicon nodules [ 7 ]. Though the pathogenesis and prevention of silicosis have been explored for many years, the exact and crucial pathogenesis has not been fully elucidated [ 8 , 9 ]. In terms of treatment, there are no specific targets for screening and diagnosis of silicosis in the early stage.…”
Section: Introductionmentioning
confidence: 99%